Development of PBL-Based E-Modules to Enhance Numerical Problem-Solving Skills among Vocational High School Students - Eky Putri Prasanti; Ahmad Fauzan; Yerizon; Yarman (Jurnal Penelitian Pendidikan IPA, 2026)
This study developed a Problem-Based Learning (PBL)-based e-module to enhance Numerical problem-solving skills among Grade X vocational high school students. Using the Plomp research and development model, the product underwent preliminary research, prototyping, and assessment phases, evaluated for validity, practicality, and effectiveness. Results indicated the e-module achieved a validity score of 3.36 (valid category) and the accompanying student worksheet scored 3.68 (very valid). Practicality assessments from students and teachers averaged 80.00%, confirming usability and accessibility via smartphones. Effectiveness testing demonstrated 76% average achievement in Numerical problem-solving, with 79.16% of students reaching minimum competency thresholds. Students showed notable improvement in problem comprehension and strategic planning, though reflective verification required further instructional scaffolding. The findings confirm that the PBL-based e-module meets established quality criteria and offers a replicable, curriculum-aligned framework for fostering active, student-centered Numericals learning in vocational education contexts.